2022
DOI: 10.1017/dmp.2022.206
|View full text |Cite
|
Sign up to set email alerts
|

Training of Medical Students for Mass Casualty Incidents Using Table-Top Gamification

Abstract: Introduction: “Table-top” exercises can improve knowledge and skills related to mass casualty incidents (MCIs) with little logistical efforts. We aim to evaluate the learning process of 5th year medical school students related to MCI response using table-top simulation and measure their methodology perception. Methods: A theoretical part plus an MCI simulation board exercise was organized. Knowledge pretest and 1 mo after posttest was scored, and an assessment questionnaire with 27 quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…“Continuous training” also appears in the top ten priorities, a fact that shows the commitment of emergency professionals to their on-going training, making it necessary to seek the best technical options in terms of new teaching methodologies. 20 , 21…”
Section: Discussionmentioning
confidence: 99%
“…“Continuous training” also appears in the top ten priorities, a fact that shows the commitment of emergency professionals to their on-going training, making it necessary to seek the best technical options in terms of new teaching methodologies. 20 , 21…”
Section: Discussionmentioning
confidence: 99%
“…Full‐scale exercises are costly, consume too much time and may interrupt clinical shifts (Chou et al, 2019; Roud et al, 2021). Tabletop exercises may be an alternative choice in which participants perform evacuation practices and use their skills to communicate with each other (Castro Delgado et al, 2022; Johnson et al, 2023). Some studies have shown that gamification learning enhances participants' level of engagement, improves their skills and optimizes their learning (Smiderle et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The WHO has emphasized preparedness for disasters and recommends regular exercise (WHO, 2019). Some studies have shown that hospital preparedness is the main factor in hospital emergency evacuation, and other studies suggest that exit drills are important and can improve disaster management (Castro Delgado et al, 2022; Hunt et al, 2020; Sahebi et al, 2021). Different types of exit drills have different pros and cons (Ciottone, 2023; Kao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allowing students to play an active role in such a crisis situation contributes positively to their professional identity. 4,5 Important factors here are the feeling that they can make a relevant contribution to patient care and be part of a team of healthcare professionals.…”
mentioning
confidence: 99%